Nonlinear free and forced vibration analysis of sandwich cylindrical panel with auxetic core and GPLRC facing sheets in hygrothermal environment. (June 2022) - Karimiasl, M.; Alibeigloo, A.
Abstract: In this study, the free and forced vibration analysis of composite sandwich panel subjected to the harmonic force excitation in the hygrothermal environment is investigated. The sandwich panel is composed of three-phase composites with polymer/Graphene platelet/fiber skins at the top and bottom surfaces and double-V auxetic honeycombs core layer with a negative Poisson's ratio. Governing equations of motion within the framework of higher-order shear deformation theory (HSDT) and von Kármán nonlinearity are obtained. Applying the generalized differential quadrature method (GDQM) and homotopy perturbation technique, respectively the linear and nonlinear equations of motion results in solving the vibration problem. In the numerical illustration, at first validation of the present formulation is carried out by comparing the numerical results with those available in the open literature. Then the effects of several parameters such as geometric parameters of double-V auxetic core, force excitation, GPL volume fraction, and different boundary conditions on the nonlinear frequencies–amplitude of sandwich panel is studied. Finally, the important findings of this research indicate that the ratio of core thickness, inclined angle, and thickness to inclined length have significant effects on nonlinear frequencies–amplitude response. Based on the results of this article designers can development of different parts of aircraft. Highlights: The free and forced vibration analysis. Sandwich cylindrical panel, composed of Graphene platelet reinforced composite (GPLRC) skins and double-V auxetic core. Using Reddy' s higher-order shear deformation theory (HSDT) and von Kármán nonlinearity. The generalized differential quadrature method (GDQM) and homotopy perturbation are applied. The ratio of core thickness, inclined angle, and thickness to inclined length have significant effects on nonlinear frequencies–amplitude response.